Design of a monitoring and safety system for underground mines using wireless sensor networks. (25th August 2019) - Jordaan, Coert; Malekian, Reza
In this paper, a mine safety system using a wireless sensor network (WSN) is implemented. Investigations are done into design of sensors and wireless communication to profile the underground mining environment. The information is used to design and implement a robust hardware-based sensor node with standalone microcontrollers that sample data from six different sensors, namely temperature, humidity, airflow speed, noise, dust and gas level sensors, and transmit the processed data to a graphical user interface. The system reliability and accuracy is tested in a simulated mine and provided linear and accurate results over nearly a month of daily testing. It is observed that critical success factors for the wireless sensor node is its robust design, which does not easily fail or degrade in performance. The node also has strong, self-adaptive networking functionality, to recover in the case of a node failure.